INVERSE PROBLEM OF ACOUSTICS - SANTOSO YUWONO (NIM: 10113045), DAVID
In this final project, we will study the inversion of acoustics to predict the physical parameters of a wave media. It is assumed that the wave propagate on one dimensional media (one can call it as a string). Before doing the inversion, one should learn about the forward problem first. With a good understanding about the forward problem, we can generate the data from the specific initial and boundary problem in the model. Here is the brief explanation about the model that will be used in this final project. Physically, a pressure will be given to one point on the media. Then, the system will be observed within an interval of time, especially at the point which the pressure has been given. After that, the behavior at that point will be recorded. With this data, physical parameter like the wave speed and the density will be computed as the solution of the inversion. To find the solution, we convert the acoustics partial differential equation into a system of non-linear Volterra integral equation. The system of integral equation will be solved iteratively. At the end, the parameters that can be predicted by this model is the product of the wave speed and the density.